Peptide decoys: a new technology offering therapeutic opportunities for breast cancer. Issue 3 (March 2020) - Mahjoubin-Tehran, Maryam; Rezaei, Samaneh; Jalili, Amin; Aghaee-Bakhtiari, Seyed Hamid; Orafai, Hossein M.; Jamialahmadi, Tannaz; Sahebkar, Amirhossein
Highlights: Breast cancer (BC) is the most common cancer in women worldwide. Many types of BC are either incurable or resistant to conventional therapies. Peptide decoys bind to certain ligands involved in BC pathogenesis. Peptide decoys suppress oncogenic signaling pathway through high-affinity binding. We present the state-of-the-art on the use of peptide decoys for BC therapy. Abstract : Breast cancer is the most common cancer among women. Absence of hormone receptors (estrogen and progesterone) and lack of overexpression of Human Epidermal Growth Factor 2 (HER2) make triple-negative breast cancer (TNBC) an aggressive subtype of breast cancer that is resistant to conventional therapies. Peptide decoys have emerged as a novel therapeutic approach for the treatment of breast cancer. Decoy peptide technology entails the use of soluble proteins or peptides, including binding proteins or inactive cell surface receptors. Peptide decoys bind to certain ligands (e.g., inflammatory cytokines) with high affinity and specificity as receptors but cannot initiate any signaling pathway that is involved in the pathogenesis of breast cancer. In this review, we discuss the use of decoy peptides as a novel therapeutic approach for breast cancer treatment.